(untitled) (Journal of Rangpur Medical College, 2023)
Background: Water, sanitation and hygiene (WASH) facilities are considered a basic human necessity for survival and well-being, without these basic needs the health condition of millions of people, especially children and women are at risk. Bangladesh is vulnerable in this regard. Objectives: The study aimed to assess household water, sanitation and hygiene facilities and practices in selected villages of Taraganj Upazilla, Rangpur. Methods: This cross-sectional study was conducted among 341 rural households from six villages of Taraganj Upazilla, Rangpur district using a pretested semi-structured questionnaire and an observation checklist. Data were collected through face-to-face interview and observing the facilities. Result: The respondents of this study were female predominant. Male: female ratio was 1:3 and their average age was 38.16(±14.03) years. Every household were using improved source of water for both drinking and other domestic purposes but only 4.7% households safely treated water for drinking and only in 17.9% households water source was found 50 feet or more from the latrine. About 70.7% respondents kept their drinking water storage container over shelf/table, covered it with lid (65.0%) and 90.4% containers were found clean during observation. Around 95.6% households used an improved toilet facility and in 45.7 % household latrine was situated in their own dwellings. Although on observation of latrines, water collection or storage facility, hand washing facility and soap or detergent availability near them were found 63.2%, 64.4% and 59.9% households respectively. Still 2.1% households had no toilet facility at all. Nearly 19.4% respondents shared their toilet facility with other households. About 90.3% households safely disposed their children’s stool. Majority of respondents told that they used soap during washing hands before meal (84.8%) and after defecation (98.2%).During observation of the site for hand washing, water supply and soap or detergent availability were found in 97.7% and 83.3% households respectively. Good practices for drinking water, sanitation and hygiene were found among 4.7%, 71.6% and 92.7% households respectively. Conclusion: These findings are suggestive of need to come up with strategies of health education and promotion to ensure that rural households understand the importance of safe treatment of drinking water, safe disposal of child’s stool and safe distance of latrine from drinking water source in order to prevent spread of diseases. Effective policies should be developed by policymakers, safe distance of latrine from drinking water source and media and communication specialists should convey clear messages for everyone, particularly illiterate rural population. J Rang Med Col. March 2023; Vol. 8, No. 2:53-58